Pengaruh Media Powerpoint Interaktif Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Pancasila Di MI Al Falah Beran - Diana Jihan Panduwinata; Lucky Amatur Rohmani; Miratu Chaeroh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research discusses whether or not there is an influence of the use of interactive PowerPoint media on student learning outcomes, especially for grade IV students. This type of research is quantitative with a one group pretest-posttest design, with the research subjects being class IV students at MI Al Falah Beran, with a total of 28 respondents. The research instruments used in this research were tests and questionnaires. The collected data was processed and analyzed using SPSS 25 for windows software. Based on the test results, students using the pretest and posttest experienced an increase, the average score for the pretest was 64.46 while the posttest was 78.80. The results of the questionnaire that have been analyzed show that there are 15 respondents out of 28 respondents who answered yes in using interactive PowerPoint media and the results of the t test show that this interactive PowerPoint media has a significant influence as seen from the sig (2-tailed) 0.000 < 0.05 . The conclusion from the test results of this research is that there is an influence of the use of interactive PowerPoint media on student learning outcomes at MI AL Falah Beran.